(untitled) (Research, Society and Development, 2020)
The role of Paralympic athletes in sports has considered being important. The consideration is based on the desire to struggle as like normal people in the field of sports. Thus, this research is conducted in purpose to comprehend the whole phenomenon of Paralympic athletes in achieving accomplishment. Descriptive qualitative is applied in purpose to reveal the condition, facts, phenomenon, variable occurred. The main purpose is to understand the phenomenon more and focusing in the whole description rather by detailing on the related variables. The technique used in this research is documentation aims to find out the information dealing with the research’s object. The Indonesian’s Paralympic athletes are able to compete in the International multi-event as like ASEAN Para Games (in the level of Southeast Asia level). However, the medal achievement is not much as expected yet. However, in in Asia level that is Asian Para Games which considered as new match, unfortunately, Indonesia has not yet succeeds to match with the big countries in Asia such as China. In Asean Para Games, athletic and swimming becomes the gold medal achievement determinant. Afterwards, the best achievement achieved by Indonesia in Paralympic Games is limited merely on bronze medals. All in all, Indonesia is able to compete in the International multi-event yet the achievement need to be more increasing.